TECHNICAL-ECONOMIC RESULTS OF INDUSTRIAL ASSIMILATION OF ARC FURNACES OF DIRECT CURRENT OF NEW GENERATION - S. V. Malinovski (Литьë и металлургия)
The information on new possibilities of organization and production of steel, cast iron, alloys on the basis of aluminium, on new equipment and technologies DPPTUNP, improving technical and economic indices of enterprises, is given.